Phase II study of panobinostat in combination with bevacizumab for recurrent glioblastoma and anaplastic glioma - Lee, Eudocia Q. (Neuro Oncol, 2015)
BACKGROUND: Panobinostat is a histone deacetylase inhibitor with antineoplastic and antiangiogenic effects in glioma that may work synergistically with bevacizumab. We conducted a multicenter phase II trial of panobinostat combined with bevacizumab in patients with recurrent high-grade glioma (HGG). METHODS: Patients with recurrent HGG were treated with oral panobinostat 30 mg 3 times per week, every other week, in combination with bevacizumab 10 mg/kg every other week. The primary endpoint was a 6-month progression-fee survival (PFS6) rate for participants with recurrent glioblastoma (GBM). Patients with recurrent anaplastic glioma (AG) were evaluated as an exploratory arm of the study. RESULTS: At interim analysis, the GBM arm did not meet criteria for continued accrual, and the GBM arm was closed. A total of 24 patients with GBM were accrued prior to closure. The PFS6 rate was 30.4% (95%, CI 12.4%–50.7%), median PFS was 5 months (range, 3–9 months), and median overall survival (OS) was 9 months (range, 6–19 months). Accrual in the AG arm continued to completion, and a total of 15 patients were enrolled. The PFS6 rate was 46.7% (range, 21%–73%), median PFS was 7 months (range, 2–10 months), and median OS was 17 months (range, 5 months–27 months). CONCLUSIONS: This phase II study of panobinostat and bevacizumab in participants with recurrent GBM did not meet criteria for continued accrual, and the GBM cohort of the study was closed. Although it was reasonably well tolerated, the addition of panobinostat to bevacizumab did not significantly improve PFS6 compared with historical controls of bevacizumab monotherapy in either cohort.